Tonsil-derived mesenchymal stromal cells produce CXCR2-binding chemokines and acquire follicular dendritic cell-like phenotypes under TLR3 stimulation. Issue 2 (June 2015) - Ryu, Jung-Hwa; Park, Minhwa; Kim, Bo-Kyung; Ryu, Kyung-Ha; Woo, So-Youn
Graphical abstract: Tonsil-derived mesenchymal stromal cells produce CXCR2-binding chemokines and inhibit B cell proliferation in vitro Highlights: Tonsil-derived mesenchymal stromal cells (T-MSCs) produced CXCR2-binding chemokines upon TLR3 stimulation. TLR3 stimulation induced CD54 expression on T-MSCs. T-MSCs inhibited B cell proliferation in vitro . Abstract: We previously isolated mesenchymal stromal cells from human tonsils (T-MSCs) and showed the potential of these cells to differentiate into the mesodermal lineage and acquire a follicular dendritic cell (FDC) phenotype under cytokine stimulation. Because these T-MSCs were originally isolated from inflamed tonsillar tissues, we were curious about their activation status in response to innate immune stimuli, such as Toll-like receptors (TLRs). Therefore, we analyzed the expression profile of TLRs in T-MSCs and stimulated the T-MSCs with TLR agonists. TLR3 stimuli induced C–C chemokine receptor type 6 expression in T-MSCs after 24 h. Furthermore, results from cytokine arrays showed increases in epithelial neutrophil-activating peptide-78/C-X-C motif chemokine (CXCL) 5, granulocyte chemotactic protein-2/CXCL6, growth-related oncogene-α/CXCL1, interleukin-8/CXCL8, and interferon gamma-induced protein-10/CXCL10. CD54 expression was also increased after TLR3 stimulation. However, co-culturing T-MSCs with human B cells did not induce B-cell proliferation. This suggests that TLR3 stimulates the differentiation of T-MSCs into FDC-like cells and induces chemokine secretion, possibly by recruiting C–X–C chemokine receptor 2-expressing immune cells. In addition, T-MSCs also appeared to exert immunomodulatory effects by inhibiting B-cell proliferation, possibly by down-regulating CD18.